2000
DOI: 10.1046/j.1365-2362.2000.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated fish oil enriched in α‐tocopherol alters plasma phospholipid and mononuclear cell fatty acid compositions but not mononuclear cell functions

Abstract: Supplementation of the diet with 3.2 g EPA plus DHA per day markedly alters plasma phospholipid and PBMC fatty acid compositions. The lack of effect of FO upon PBMC functions may relate to the level of alpha-tocopherol included in the supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
241
3
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(272 citation statements)
references
References 51 publications
22
241
3
6
Order By: Relevance
“…Intervention studies have shown that changes in EPA occur mainly at the expense of AA and LA (von Schacky et al, 1985;Katan et al, 1997). Similar observations were made for peripheral blood mononuclear cells (PBMC) (Gibney & Hunter, 1993;Yaqoob et al, 2000). Owing to the usually low amount of available immune competent cells in epidemiological studies we chose RBC membranes as a proxy.…”
Section: Discussionmentioning
confidence: 91%
“…Intervention studies have shown that changes in EPA occur mainly at the expense of AA and LA (von Schacky et al, 1985;Katan et al, 1997). Similar observations were made for peripheral blood mononuclear cells (PBMC) (Gibney & Hunter, 1993;Yaqoob et al, 2000). Owing to the usually low amount of available immune competent cells in epidemiological studies we chose RBC membranes as a proxy.…”
Section: Discussionmentioning
confidence: 91%
“…Kelley et al (1999) have reported inhibition of NK cell activity following 6 g DHA/d in young males. In contrast, Yaqoob et al (2000) have found no effect of 3 . 3 g EPA + DHA/d on NK cell activity in a mixed group of healthy subjects.…”
Section: Effects Of Epa and Dha On Natural Killer Cell Activitymentioning
confidence: 87%
“…They do this by decreasing the amount of AA in membrane phospholipids and competitively inhibiting the production of AA-derived eicosanoids from COX and 5-LOX [44]. For example, when healthy subjects were supplemented with fish oil providing 2.1g EPA + 1.1g DHA/d for 12 weeks, the amount of AA in plasma phospholipids and mononuclear cells decreased by 20% while that of EPA increased, altering the ratio of AA:EPA from 23:1 to 1.5:1 in plasma phospholipids and from 28:1 to 6:1 in mononuclear cells [45].…”
Section: Metabolism Of Pufas and Formation Of Eicosanoidsmentioning
confidence: 99%